Global Academic Interest Scale for Undergraduate and Graduate Students. (April 2021) - Lee, Jihyun; Durksen, Tracy L.
Using an established global academic interest scale, academic interest dimensions of undergraduate ( n = 326) and graduate ( n = 401) students were compared. The four-factor structure, consisting of passion for learning, confidence in the future, career aspiration, and self-expression, held for both student groups. However, the item scores and mean factor scores as well as the pattern of factor correlations differed between the two groups. While the sample of graduate students exhibited greater levels of passion for learning, the undergraduate students showed higher levels of confidence in the future. Overall, a broad range of correlates of academic interest employed in this study provided construct validity evidence of academic interest, supporting the main tenants of the motivational theory of life-span development. Limitations and directions for future work are discussed.